Corrosion behavior of fluorinated carbonyl iron-hydrophobic composites in neutral salt spray environment. (January 2023) - Jiang, Xianyu; Zhang, Linbo; Yin, Liangjun; Yang, Guang; Xie, Jianliang; Zhang, Li; Lu, Haipeng; Liang, Difei; Deng, Longjiang
Abstract: We studied the anti-corrosion of carbonyl iron (CI) and fluorinated carbonyl iron-hydrophobic composites (CI@PFOTES) under the application of a neutral salt spray. The results show that various corrosion products (Fe2 O3, FeOOH, Fe3 O4 et.al) appeared after subjecting the samples to 192 h of corrosion and reveals the corrosion process: Fe → Fe 2 + → Fe 3 + . In contrast, CI@PFOTES composites possesses minor corrosion characteristics due to hydrophobic of PFOTES coating. But, the protective layer also existed partial failure due to hydrolysis aging effect. For electromagnetic properties, the downward trend of CI is more severe than CI@PFOTES due to forming various weak magnetic phase oxidation products. Graphical Abstract: ga1 Highlights: Corrosion mechanism of fluorinated carbonyl iron-hydrophobic composites are explored in neutral salt spray. In-situ XPS depth profile reveals the carbonyl iron micron particles corrosion process: Fe → Fe 2 + → Fe 3 + . Fluorinated carbonyl iron-hydrophobic composites show improved corrosion resistance, but also suffer from hydrolytic aging. Carbonyl iron exhibit a decreased electromagnetic property due to forming various weak magnetic phase oxidation products.